Fvc, Fev1 and Fev1/Fvc % in Female SLE Patients and Their Relationship with Duration of the Disease (Medicine Today, 2014)
Systemic Lupus Erythematosus (SLE) is an autoimmune disorder which affects multiple organs of human including lungs. To assess FVC, FEV1 and FEV1/FVC % in SLE patients and to correlate them with the duration of the disease. This cross-sectional study was carried out in the Department of Physiology, BSMMU, Dhaka, from January 2010 to December 2010. A total number of 120 female subjects were selected, among which 30 were age and BMI matched apparently healthy subjects for comparison (control) and 90 were patients of SLE ( study group) . Ages of all the patients were ranged from 20 to 50 years and they were matched in terms of age, sex and BMI. Based on the duration of the disease, patients were subdivided into B1 (1-6 months), B2 (2-5 years) and B3 (6-10 years). Controls were selected from the community and the patients from the Out Patient Department (OPD) of SLE clinic, Department of Medicine, BSMMU, Dhaka. Lung function were assessed by measuring Forced vital capacity (FVC), Forced expiratory volume in 1st second (FEV1), Forced expiratory ratio (FEV1/FVC%) with a Digital MicroDL spirometer. For statistical analysis Independent Sample t test, One way ANOVA test and Pearsons correlation coefficient test were performed as applicable. The mean percentage of predicted values of lung function parameters in healthy female subjects were within normal ranges. The mean percentage of predicted values of FVC, FEV1 were significantly lower in all study groups when compared to control. Again, the mean percentage of predicted values of FVC, FEV1 significantly lower in the patients of Group B3 compared to Group B2 except FVC which were non significantly lower. Moreover, these comparisons were significantly lower when compared to Group B1. The differences of the mean percentage of predicted values of FVC, FEV1 were significantly lower in Group B2 when compare to Group B1. In addition, FVC and FEV1 were positively correlated in B2 and B3 when correlated with duration of SLE. All these values were statistically non significant. In addition The mean percentage of predicted values of FEV1/ FVC% were almost similar and the differences among the groups were statistically non-significant. Pulmonary function decrease in SLE female and the reduction is inconsistently associated with duration of the disease. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21307 Medicine Today 2014 Vol.26(1): 22-27